The impact of risks management in the success of JIT implementation: Structural equations modeling for relational analysis in the Moroccan industry. Issue 4 (2nd October 2021) - Sebtaoui, Fatima Ezzahra; Adri, Ahmed; Rifai, Said; Sahaf, Kenza
Abstract: For more than 30 years, supply chain management adopts just-in-time (JIT) strategy. The adoption of JIT has reduced wastes and total costs; however it leads to complexity and risks. Thus, top management has to recognize and address critical risks in JIT implementation. This is the main objective of this study, which aims at investigate the activities related to risk management in JIT implementation and their relation with critical success factors (CSFs) or the key activities executed during JIT implementation and the benefits obtained. The research model was evaluated using the structural equations modeling (SEM) with the LISEREL approach. The results forthcoming from the study shows that risk treatment is one of the most important factors for the successful JIT implementation, and that other factors, such as good relationship with suppliers, management commitment, and management of human resources, depend upon it.